A Cross-Temporal Meta-Analysis on Marital Satisfaction of Chinese Couples - Li, Fengzhan; Chen, Chen; Wang, Jinrui; Peng, Haiyun; Wu, Lin; Ren, Lei; Song, Lei; Jin, Yinchuan; Yang, Qun (Frontiers in Psychology, 2022)
Objective: To investigate the changing trend of Chinese couples’ marital satisfaction and its relationship with social changes. Methods: A cross-temporal meta-analysis was performed on 118 original studies (n=31909) reporting marital satisfaction of Chinese couples from 1994 to 2020, primarily using correlation analysis and regression analysis. Results: 1) Overall, the marital satisfaction of Chinese couples showed a downward trend over the period. 2) Men’s marital satisfaction displayed almost no change, while women’s marital satisfaction had a more obvious downward trend. 3) Changes in macrosocial factors (per capita consumption expenditure, housing prices, old-age dependency ratio, and divorce rate) could significantly predict the downward trend of marital satisfaction, especially for women. Conclusion: In the past 27 years, the overall marital satisfaction level of Chinese couples has shown a downward trend, and there are gendered differences, which may be related to changes in the socioeconomic and cultural environments.